A rhodamine–naphthalimide–benzamide trichromophoric system with solid-state and multiple solvent dependent aggregate emissive properties. (19th May 2021) - Sharma, Hemant; Hearn, Kyle N.; Ranieri, Anna Maria; Caporale, Chiara; Massi, Massimiliano; Pfeffer, Frederick M.
Abstract : The readily synthesised rhodamine–naphthalimide–benzamide trichromophoric system forms unique AIE emissive species in DMSO solutions with traces of water (<1%) and high water content (>50%) and responds to pH changes in both solution and solid state. Abstract : A multiresponsive rhodamine–naphthalimide–benzamide conjugate was synthesised in high yield in three steps. The trichromophoric system formed emissive aggregates in pure DMSO that were remarkably sensitive to traces of water (<1%). High water content (>50%) was also indicated with unique AIE emissive species identified in both the pure DMSO and 1 : 1 DMSO : water solutions. The design of the probe also enabled a unique response to both high and low pH and this pH sensitive AIE behaviour was also evident in the solid state.